2009
DOI: 10.1590/s1517-83822009000200034
|View full text |Cite
|
Sign up to set email alerts
|

In vitro establishment and propagation of a Brazilian strain ofAnaplasma marginale with appendage in IDE8 (Ixodes scapularis) cells

Abstract: A Brazilian isolate of Anaplasma marginale with appendage was successfully established and maintained in vitro in a tick cell line (IDE8). Infection was confirmed by optical and transmission electron microscopy. In addition, primers MSP1aNF2 and MSP1aNR2 amplified products from DNA extracted from infected IDE8 cells. Comparisons with partial sequences of the msp1α gene and the complete genome of A. marginale confirmed that the sequences of amplified fragments were from the A. marginale genome. This is the firs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
7
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 17 publications
3
7
1
Order By: Relevance
“…the organisms and thus slowing down culture development. Otherwise, the development of the colonies in the tick cells was similar to that already described (Bastos et al, 2009;Blouin et al, 2000). The sequence of the msp1˛ gene of A. marginale from both cattle remained the same after passage in IDE8 tick cell line.…”
Section: Repeatsupporting
confidence: 81%
See 2 more Smart Citations
“…the organisms and thus slowing down culture development. Otherwise, the development of the colonies in the tick cells was similar to that already described (Bastos et al, 2009;Blouin et al, 2000). The sequence of the msp1˛ gene of A. marginale from both cattle remained the same after passage in IDE8 tick cell line.…”
Section: Repeatsupporting
confidence: 81%
“…First colonies were detected 60 days after culture initiation. The time until first detection, however, was considerably longer than reported in other studies (Bastos et al, 2009;Blouin et al, 2000;Munderloh et al, 1996) where periods between 8 and 34 days were observed. The reasons for this could have been manifold.…”
Section: Discussioncontrasting
confidence: 56%
See 1 more Smart Citation
“…marginale cultures can be initiated from blood obtained from infected calves during ascending rickettsemia (BLOUIN et al, 2000;BASTOS et al, 2009). Blood samples are collected with anticoagulant, and usually the blood cells are washed and subsequently cryopreserved in liquid nitrogen using DMSO as cryoprotectant.…”
Section: Culture Initiation and Propagation Of Anaplasma Marginalementioning
confidence: 99%
“…Culturing of Brazilian strains of A. marginale in IDE8 cells was described previously (BASTOS et al, 2009). Briefly, monolayers of IDE8 cells were inoculated with blood containing UFMG1 and UFMG2 isolates from A. marginale that had been cryopreserved in liquid nitrogen.…”
Section: Preparation Of Inactivated Vaccine From Anaplasma Marginalementioning
confidence: 99%